Synonymy of Leonomyrma Arnoldi 1968 With Chalepoxenus Menozzi 1922 (Hymenoptera: Formicidae) - Alfred Buschinger (Psyche: A Journal of Entomology)
Arnoldi (1968) erected the genus Leonomyrma for a single new species, L. spinosa, which he had collected in July, 1949, near Peremetriaja, East-Kasachstan (USSR), at the lower course of Ural River. Up until present, only the type series of 4 ♀♀ and 14 ♂♂ have been known; no ☿☿ were found. In the course of a study in morphology and behavior of several species of the ant genus Chalepoxenus, I came across the description of Leonomyrma. A direct comparison of its holotype (♀) and an allotype (♂) with material of two Chalepoxenus species, C. muellerianus (Finzi) (= C. gribodoi Menozzi) and C. kutteri Cagniant, clearly revealed the synonymy of the two genera.